Analisis Keselamatan dan Keamanan Di Stasiun Manggarai Sebagai Simpul Konektivitas Berdasarkan Standar Pelayanan Minimum dan Persepsi Penumpang - Wardani, Ayu; Irawan, Muhammad Zudhy; Priyanto, Sigit (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2024)
Manggarai Station serves as a transit hub for both commuter and airport trains, making it the busiest and the most crowded train station in Jakarta. This situation can lead to safety and security issues. This research was conducted to assess the safety and security facilities at Manggarai railway station and determine their compliance with the Minimum Service Standards for Railway Passenger Transport, comparing them with passengers' perceptions of the safety and security facilities. The analytical methods used in this research were crosstab analysis and Importance Performance Analysis (IPA). Crosstab analysis was employed to examine the relationship between respondents' socio-demographic characteristic and travel characteristics, as well as their relationship with safety and security variables at the station. IPA was used to assess the quality of safety and security facility performance at Manggarai Station based on passengers' perceptions. The research findings indicated that several safety and security facilities at Manggarai Station unable to meet the Minimum Service Standards for Railway Passenger Transport. These included wide gaps between platforms and train bodies, uneven platform and train floors, inadequate information and assembly points, and narrow and obstructed pathways within the station. According to passengers' perceptions, there were five attributes of safety and security facility performance that had low ratings: gaps between platforms and train bodies, platform and train floors, escalators, assembly points, and barriers between platforms and trains. safety, security, manggarai station, passenger perseptions, minimum service standards